Fruiting bodies yield of oyster mushroom (Pleurotus columbinus) as affected by different portions of compost in the substrate - Mohamed Fouad Mohamed; Emad F. S. Refaei; Mohamed M. A. Abdalla; Sayed H. Abdelgalil (International Journal of Recycling of Organic Waste in Agriculture)
Purpose A study was conducted to assess production of Pleurotus columbinus mushroom fruiting bodies for different formulations of rice or corn straw substrates mixed at different percent portions with the corresponding composted straw. Methods These formulations were: (1) raw straw (RS) mixed with 5 % composted straw (CS), (2) RS mixed with 10 % CS, (3) RS mixed with 15 % CS, (4) RS mixed with 25 % CS, (5) RS mixed with 50 % CS, and (6) 100 % RS. Composted straw (CS) was made of moistened chopped RS mixed with chicken manure and soil (4:1:1, v/v). Results Data showed a magnificent impact of the substrate on oyster mushroom fruiting bodies yield and characteristics. There was a significant progressive upgrading in all parameters studied of mushroom growth and crop outcome with increasing the percentage of CS mixed with the RS substrate up to 15 %. Utilizing CS at 25 % significantly downgraded these parameters. No mushroom growth was observed at all when cultivated in medium contained 50 % CS. Instead, molds of different colors grew on that latter substrate mixture. The formulation containing 15 % CS distinctly gave the uppermost fruiting bodies yield, biological efficiency, earliness for pinheads formation, fruiting body cap diameter, thickness and weight and stem diameter, length and weight. Up to 80 % increase in fruiting bodies crop outcome relative to sole RS was detected. Conclusions This study suggests that composted straw substrates hold a great promise for the development of Pleurotus mushroom production industry